The Correlation Between Nutritional Status and The Incidence of Hypertension in Productive Age - Utma Nidiya Pangesti; Aisah Aisah; Mila Triana Sari (Journal of Health and Nutrition Research, 2023)
Hypertension is when blood vessels have high blood pressure, systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg. The prevalence of hypertension globally is 22% of the total world population. Basic health research 2018 reported that the incidence of hypertension was 34.1%. The Jambi City Health Office reported the number of hypertension cases at 25,846 cases, and data from the Simpang IV Sipin Health Center in Jambi City showed the number of people with hypertension in January-March as many 652 cases. This study aims to determine the factors associated with the incidence of hypertension in productive age at the Simpang IV Sipin Health Center in Jambi City. The design used in this study is a quantitative research with a cross sectional approach. This research was conducted at the Simpang IV Sipin Health Center in January-June 2023. The population in this study is patients who visited the Simpang IV Sipin Health Center, with a total of 96 people in January-March 2023. The sample amounted to 53 respondents. The sampling technique is accidental sampling. The data analysis used was univariate and bivariate analysis using chi-square statistical test. The results of this study are that there is a relationship between nutritional status (0.022) with the incidence of hypertension in productive age at the Simpang IV Sipin Health Center. In this study, it can be concluded that there is a relationship between nutritional status and the incidence of hypertension at productive age, so the researchers recommend that the Simpang IV Sipin Health Center in Jambi City provide health education to hypertension sufferers with the theme "Ideal body weight as a first step in preventing and treatment of hypertension”.